2010
DOI: 10.1186/1472-6939-11-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of group counseling with individual counseling in the comprehension of informed consent: a randomized controlled trial

Abstract: BackgroundStudies on different methods to supplement the traditional informed consent process have generated conflicting results. This study was designed to evaluate whether participants who received group counseling prior to administration of informed consent understood the key components of the study and the consent better than those who received individual counseling, based on the hypothesis that group counseling would foster discussion among potential participants and enhance their understanding of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Sarkar et al tested a focus group intervention with parents in rural India, finding no significant improvement [13]. Aaronson et al, conversely, found significant improvement with extra phone conversations [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarkar et al tested a focus group intervention with parents in rural India, finding no significant improvement [13]. Aaronson et al, conversely, found significant improvement with extra phone conversations [29].…”
Section: Resultsmentioning
confidence: 99%
“…Preferences between interventions and controls were either insignificant or showed that participants significantly preferred the interventions [19,27,29,32,35,43,47,52-54]. Accrual rates, tracked for trials with real parent studies, were also reported as improved or unchanged by interventions in all categories [13,23,29,43,52,55,56], with one exception [46]. These findings are consistent with those discussed in the 2004 review [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that over 80% of subjects in the developing world do not understand basic concepts such as placebo, randomization and the ability to withdraw from a study at any time without negative consequences. 22 Questions arise as to why these possibilities do not influence IRB deliberations more, and whether IRBs consider or ignore this evidence. The fact that at a certain point, IRBs may be seeking to follow regulations more than protecting human subjects poses critical questions that require additional research.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2004, there have been several intervention studies to increase informed consent understanding in clinical trials, but the majority has assessed specifics of a clinical trial rather than on the eight basic elements of informed consent (Campbell, Goldman, Boccia, & Skinner, 2004; Hutchison, Cowan, & Paul, 2007; Moseley, Wiggins, & O’Sullivan, 2006; Olver, Whitford, Denson, Peterson, & Olver, 2009; Sarkar et al, 2010; Wray, Stryker, Winer, Demetri, & Emmons, 2007). While we do not view HIV/AIDS clinical trials as unique in their informed consent process, we do know that there currently are over 1000 HIV/AIDS clinical trial protocols, with numerous sites per protocol, actively, or soon to be recruiting potential subjects both nationally and internationally (NIH, 2010).…”
Section: Introductionmentioning
confidence: 99%